HIGH PRESSURE AND HIGH TEMPERATURE METAL-SILICATE PARTITIONING OF SIDEROPHILE ELEMENTS: THE IMPORTANCE OF SILICATE LIQUID COMPOSITION - Drake M.J.; Rubie D.C.; Hillgren V.J. (My University, 1996)
We have determined liquid metal-liquid silicate partition coefficients for Ni, Co, Mo, W, P, Ga, and Ge at 10 GPa and 2000°C in a multi-anvil apparatus. Our sample containers were either MgO or Al2O3. The two different capsule materials imposed different redox states on our samples as well as producing very different silicate liquid compositions. The samples run in Al2O3 containers were at an fO2 1.1–1.4 log units below the iron-würstite (IW) buffer, and samples run in the MgO containers were 2.3 log units below the IW buffer. Although the partition coefficients we determine for Ni, Co, Mo, and W agree well with our previous work, we have obtained some rather surprising results. In the experiments reported here the partition coefficients for W, P, and Ge decrease with decreasing oxygen fugacity which is opposite to what is expected. We also find that partition coefficients for Mo and Ga do not increase as much as expected with decreasing oxygen fugacity, and although Ni and Co behave in a more normal manner, their partition coefficients also do not increase as much as expected with decreasing oxygen fugacity as a +2 valence for the two elements would predict. Simple analysis of the structures of the two different silicate melts shows that the MgO-rich melt is considerably more depolymerized than the Al2O3-rich melt. The partitioning behavior of all the elements indicates that all the cations are stabilized in the more depolymerized MgO-rich melt. This is in accord with previous work on compositional effects on forsterite-liquid partitioning and the partitioning of metal cations between immiscible silicate liquids. Our results emphasize the need for thorough investigation of all variables that could potentially effect partitioning including the composition of the silicate melt. In addition, they suggest that mantle composition may play an important role during core formation.